In-Vitro and In-Silico Study: The Anti-Inflammatory Activity of Ethanol Extract from Cogon Grass Roots (Imperata cylindrica L. - Warnasih, Siti; Hasanah, Uswatun; Simalango, Siska Juliani; Mulyati, Ade Heri; Widiastuti, Diana (Universitas Airlangga, 2025)
Background: Inflammation is a protective reaction triggered by harmful substances, microbes, or physical trauma. Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used to treat inflammation, though they have certain drawbacks, such as the potential for chronic kidney failure and unfavorable gastrointestinal side effects. Therefore, alternative treatments are needed. Cogon grass (Imperata cylindrica L.) roots contain secondary metabolites that may offer potential for inflammation treatment. Objective: This study aims to investigate the potential of secondary metabolites from cogon grass roots as anti-inflammatory agents, both in vitro using protein denaturation inhibition techniques and in silico against the COX-1 and COX-2 enzyme receptors. Methods: Molecular docking of COX-1 (PDB ID 6Y3C) and COX-2 (PDB ID 1PXX) using AutoDock Tool 1.5.6 was used to test the anti-inflammatory activity. In parallel, the in vitro technique involved spectrophotometric denaturation inhibition of the BSA (bovine serum albumin) protein. Results: The in silico results showed that the cyclovalone ligand exhibited the highest interaction and stability, with Gibbs free energies of -9.3 kcal/mol against COX-1 and -9.8 kcal/mol against COX-2, compared to the control ligand diclofenac, which had Gibbs free energies of -6.5 kcal/mol against COX-1 and -8.5 kcal/mol against COX-2. The 30% ethanol extract of cogon grass roots demonstrated anti-inflammatory activity in the in vitro analysis, with an IC50 value of 71.79 µg/mL. Conclusions: These preliminary findings suggest that the ethanol extract of cogon grass roots contains cyclovalone compounds with potential as anti-inflammatory agents.